Устойчивость трансгенных растений табака к неблагоприятной температуре в ряду поколений - Нурминская, Ю.В.; Максимова, Л.А.; Копытина, Т.В.; Еникеев, А.Г. (Фактори експериментальної еволюції організмів, 2014)
Aims. Were assessed the fluctuating asymmetry level and morphometric parameters of tobacco plants, transformed by gene nptII. Plants were grown under normal (+25°) and extremal (+15°, +35°С) conditions. Methods. The level of fluctuating was estimated how a difference between left and right halves of the leaf. Results.Transgenic plants were more low temperature-sensitive then control ones, these plants demonstrated decreased morphometric parameters and raised fluctuating asymmetry level, T5 and T6 generations particularly. Conclusions. Coadapted gene complexes are the base of organism adaptation. Low rate of stress adaptation ability of transgenic plants can be the result of transformation procedure, which had perturbed gene complexes work.